The long road to sustainability : the past, present, and future of international environmental law and policy - Gillespie, Alexander (Oxford : Oxford University Press, 2018)
For the last few thousand years, humanity has struggled to achieve sustainable development. Alexander Gillespie sees the problem as multi-faceted: a three legged stool of economic, social, and environmental conundrums have stalled the quest for the long term viability of both our species and the ecosystems in which we reside. Gillespie moves from the low life expectancy, excessive deforestation, and wetland drainage of the medieval period, through the species loss, coal burning, free trade, and poor waste management of the 17th and 18th centuries, and to the more recent concerns of climate change, unsustainable fisheries, and chemical pollutants. By delivering a comprehensive examination of human survival over the past millennium, Gillespie illustrates that the challenges we face are not new - that we now have the means to counter them, is.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 28, 2018).
Keywords: Natural resources -- History; Sustainability; Environmental law; Environment and Ecology; The environment